Consistency and reliability of smoking-related variables: longitudinal study design in asthma and COPD. Issue 1 (1st January 2019) - Hirvonen, Eveliina; Stepanov, Mikhael; Kilpeläinen, Maritta; Lindqvist, Ari; Laitinen, Tarja
ABSTRACT: Introduction : Smoking has a significant impact on the development and progression of asthma and chronic obstructive pulmonary disease (COPD). Self-reported questionnaires and structured interviews are usually the only way to study patients' smoking history. In this study, we aim to examine the consistency of the responses of asthma and COPD patients to repeated standardised questions on their smoking habits over the period of 10 years. Methods : The study population consisted of 1329 asthma and 959 COPD patients, who enrolled in the study during years 2005–2007. A follow-up questionnaire was mailed to the participants 1, 2, 4, 6, 8, and 10 years after the recruitment. Results : Among the participants who returned three or more questionnaires ( N = 1454), 78.5 % of the patients reported unchanged smoking status (never smoker, ex-smoker or current smoker) across the time. In 4.5% of the answers, the reported smoking statuses were considered unreliable/conflicting (first never smoker and, later, smoker or ex-smoker). The remainder of the patients changed their status from current smoker to ex-smoker and vice versa at least once, most likely due to struggling with quitting. COPD patients were more frequently heavy ex- or current smokers compared to the asthma group. The intraclass coefficient correlations between self-reported starting (0.85) and stopping (0.94) years as well as the consumption of cigarettes (0.74) over time showed good reliability among both asthma and COPD patients. Conclusion : Self-reported smoking data among elderly asthma and COPD patients over a 10-year follow-up is reliable. Pack years can be considered a rough estimate for their comprehensive consumption of tobacco products over time. We also observed that the questionnaire we used was not designed for dynamic changes in smoking which are rather common among heavy smokers especially when the follow-up time is several years, as in our study.